TLR7 Signaling Shapes and Maintains Antibody Diversity Upon Virus-Like Particle Immunization - Chang, Xinyue; Krenger, Pascal; Krueger, Caroline C.; Zha, Lisha; Han, Jiami; Yermanos, Alexander; Roongta, Salony; Mohsen, Mona O.; Oxenius, Annette; Vogel, Monique; Bachmann, Martin F. (Frontiers in Immunology, 2022)
Virus-like particles (VLPs) are used in different marketed vaccines and are able to induce potent antibody responses. The innate pattern recognition receptors TLR7/8 recognize single stranded (ss) RNA naturally packaged into some VLPs and have been shown to enhance the production of IgG antibodies upon immunization. Here we demonstrate that, upon immunization with RNA-loaded bacteriophage-derived VLP Qb, TLR7 signaling accelerates germinal center formation, promotes affinity/avidity maturation of VLP-specific IgG and isotype switching to IgG2b/2c. These findings extrapolated to antigens displayed on Qb as Fel d 1, the major cat allergen, chemically attached to Qb also induced higher affinity/avidity IgG2b/2c antibodies in a TLR7-dependent fashion. Chimeric mice lacking TLR7-expression exclusively in B cells demonstrated that the enhanced IgG responses were driven by a B cell intrinsic mechanism. Importantly, deep sequencing of the BCR repertoire of antigen-specific B cells demonstrated higher diversity in mice with TLR7 signaling in B cells, suggesting that TLR7-signaling drives BCR repertoire development and diversity. Furthermore, the current data demonstrate that high levels of clonal diversity are reached early in the response and maintained by TLR7 signaling. In conclusion, TLR7 signaling enhances levels and quality of IgG antibodies, and this finding has major implications for vaccine design.